2017
DOI: 10.3390/nu9010073
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Smartphone Image-Based Dietary Assessment Method for Pregnant Women

Abstract: Image-based dietary records could lower participant burden associated with traditional prospective methods of dietary assessment. They have been used in children, adolescents and adults, but have not been evaluated in pregnant women. The current study evaluated relative validity of the DietBytes image-based dietary assessment method for assessing energy and nutrient intakes. Pregnant women collected image-based dietary records (via a smartphone application) of all food, drinks and supplements consumed over thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
81
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(91 citation statements)
references
References 32 publications
(37 reference statements)
8
81
2
Order By: Relevance
“…One study used a note-taking app with image capture (52). Others had study participants record the consumption of pre-defined food types or food groups [54-56, 58, 60].…”
Section: Data Collection Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…One study used a note-taking app with image capture (52). Others had study participants record the consumption of pre-defined food types or food groups [54-56, 58, 60].…”
Section: Data Collection Methodsmentioning
confidence: 99%
“…In Seto and colleagues' [59] 6-day study, 72 food items were reported via video per participant. Participants on average reported 7 food entries via dietary record per day in Ashman and colleagues' 3-day study [52]. Two studies used alternative methods to capture missed meals (ie, pen-and-pencil or voice recording).…”
Section: Data Collection Methodsmentioning
confidence: 99%
See 3 more Smart Citations